2022
DOI: 10.1088/1361-6587/ac5ae8
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and modelling of momentum transport based on NBI modulation experiments at ASDEX Upgrade

Abstract: The prediction of the plasma rotation is of high interest for fusion research due to the effects of the rotation upon MHD instabilities, impurities, and turbulent transport in general. In this work, an analysis method was studied and validated to reliably extract momentum transport coefficients from NBI modulation experiments. To this end, a set of discharges was created with similar background profiles for the ion and electron temperatures, the heat fluxes, the electron density, and the plasma rotation that, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 92 publications
1
24
0
Order By: Relevance
“…neoclassical corrections are not applied. Previous works on a similar discharge showed that possible offset corrections can, partly, be compensated for via the boundary condition given [33]. Neoclassical corrections in gradients were observed to be smaller than experimental uncertainties and have no effect on the assessed Pr and −RV c /χ φ .…”
mentioning
confidence: 71%
See 1 more Smart Citation
“…neoclassical corrections are not applied. Previous works on a similar discharge showed that possible offset corrections can, partly, be compensated for via the boundary condition given [33]. Neoclassical corrections in gradients were observed to be smaller than experimental uncertainties and have no effect on the assessed Pr and −RV c /χ φ .…”
mentioning
confidence: 71%
“…The inclusion of this time dependence becomes critical to the analysis, as will be shown herein, but was neglected in previous analyses [25,35,38]. This resulted in discrepancies between the experimentally inferred and gyrokinetically predicted momentum transport coefficients [25,33,35,38] rendering extrapolation to future devices problematic. In this work, none of the mechanisms is fixed to theory predictions, the intrinsic torque is included and full time dependencies are retained in all of the transport coefficients and kinetic profiles, in contrast to the previous work [33] of the authors.…”
mentioning
confidence: 98%
“…As discussed earlier [33], NBI modulation is the method of choice to assess momentum transport coefficients in Hmode plasmas on AUG. The modulation of a single NBI source with reduced power (P H mod ≈ 1.1 MW and P D mod ≈ 0.7 MW) was a good compromise between providing a well resolved rotation modulation and limiting the perturbation in the other transport channels.…”
Section: Experimental Descriptionmentioning
confidence: 99%
“…where all notations will be explained in the following section, is used to fit all terms on the right-hand side with experimental measurement [13,[21][22][23]. In this effort, any fittings without the RS torque density (∇ • Π RS ) included is never sufficient to explain the experimental observations [23]. Thus, predicting proper magnitudes of RS torques is an important step in momentum transport study, as emphasized in [23].…”
Section: Introductionmentioning
confidence: 99%